Moral autopsy : truths, secrets, and the judicial afterlives of communist secret service archives / Saygun Gökarıksel. - Gökarıksel, Saygun (Cambridge Studies in Law and Society., 2025)
While communism was proclaimed dead in Eastern Europe around 1989, archives of communist secret services lived on. They became the site of judicial and moral examination of lives, suspicions of treason or 'collaboration' with the criminalized communist regime, and contending notions of democracy, truth, and justice. Through close study of court trials, biographies, media, films, and plays concerning judges, academics, journalists, and artists who were accused of being communist spies in Poland, this critical ethnography develops the notion of moral autopsy to interrogate the fundamental problems underlying global transitional justice, especially, the binary of authoritarianism and liberalism and the redemptive notions of transparency and truth-telling. It invites us to think beyond Eurocentric teleology of transition, capitalist nation-state epistemology and prerogatives of security and property, and the judicialized and moralized understanding of history and politics.